Mechanical stretch promotes apoptosis and impedes ciliogenesis of primary human airway basal stem cells - Li-Qin Lin; Hai-Kang Zeng; Yu-Long Luo; Di-Fei Chen; Xiao-Qian Ma; Huan-Jie Chen; Xin-Yu Song; Hong-Kai Wu; Shi-Yue Li (Respiratory Research, 2023)
Abstract Background Airway basal stem cells (ABSCs) have self-renewal and differentiation abilities. Although an abnormal mechanical environment related to chronic airway disease (CAD) can cause ABSC dysfunction, it remains unclear how mechanical stretch regulates the behavior and structure of ABSCs. Here, we explored the effect of mechanical stretch on primary human ABSCs. Methods Primary human ABSCs were isolated from healthy volunteers. A Flexcell FX-5000 Tension system was used to mimic the pathological airway mechanical stretch conditions of patients with CAD. ABSCs were stretched for 12, 24, or 48 h with 20% elongation. We first performed bulk RNA sequencing to identify the most predominantly changed genes and pathways. Next, apoptosis of stretched ABSCs was detected with Annexin V-FITC/PI staining and a caspase 3 activity assay. Proliferation of stretched ABSCs was assessed by measuring MKI67 mRNA expression and cell cycle dynamics. Immunofluorescence and hematoxylin-eosin staining were used to demonstrate the differentiation state of ABSCs at the air-liquid interface. Results Compared with unstretched control cells, apoptosis and caspase 3 activation of ABSCs stretched for 48 h were significantly increased (p < 0.0001; p < 0.0001, respectively), and MKI67 mRNA levels were decreased (p < 0.0001). In addition, a significant increase in the G0/G1 population (20.2%, p < 0.001) and a significant decrease in S-phase cells (21.1%, p < 0.0001) were observed. The ratio of Krt5+ ABSCs was significantly higher (32.38% vs. 48.71%, p = 0.0037) following stretching, while the ratio of Ac-tub+ cells was significantly lower (37.64% vs. 21.29%, p < 0.001). Moreover, compared with the control, the expression of NKX2-1 was upregulated significantly after stretching (14.06% vs. 39.51%, p < 0.0001). RNA sequencing showed 285 differentially expressed genes, among which 140 were upregulated and 145 were downregulated, revealing that DDIAS, BIRC5, TGFBI, and NKX2-1 may be involved in the function of primary human ABSCs during mechanical stretch. There was no apparent difference between stretching ABSCs for 24 and 48 h compared with the control. Conclusions Pathological stretching induces apoptosis of ABSCs, inhibits their proliferation, and disrupts cilia cell differentiation. These features may be related to abnormal regeneration and repair observed after airway epithelium injury in patients with CAD.